Lipid Emulsions Differentially Affect LPS‐Induced Acute Monocytes Inflammation: In Vitro Effects on Membrane Remodeling and Cell Viability. Issue 11 (20th July 2014) - Boisramé‐Helms, Julie; Delabranche, Xavier; Klymchenko, Andrey; Drai, Jocelyne; Blond, Emilie; Zobairi, Fatiha; Mely, Yves; Hasselmann, Michel; Toti, Florence; Meziani, Ferhat
Abstract: The aim of this study was to assess how lipid emulsions for parenteral nutrition affect lipopolysaccharide (LPS)‐induced acute monocyte inflammation in vitro. An 18 h long LPS induced human monocyte leukemia cell stimulation was performed and the cell‐growth medium was supplemented with three different industrial lipid emulsions: Intralipid ®, containing long‐chain triglycerides (LCT—soybean oil); Medialipid ®, containing LCT (soybean oil) and medium‐chain triglycerides (MCT—coconut oil); and SMOFlipid ®, containing LCT, MCT, omega‐9 and ‐3 (soybean, coconut, olive and fish oils). Cell viability and apoptosis were assessed by Trypan blue exclusion and flow cytometry respectively. Monocyte composition and membrane remodeling were studied using gas chromatography and NR12S staining. Microparticles released in supernatant were measured by prothrombinase assay. After LPS challenge, both cellular necrosis and apoptosis were increased (threefold and twofold respectively) and microparticle release was enhanced (sevenfold) after supplementation with Medialipid ® compared to Intralipid ®, SMOFlipid ® and monocytes in the standard medium. The monocytes differentially incorporated fatty acids after lipid emulsion challenge. Finally, lipid‐treated cells displayed microparticles characterized by disrupted membrane lipid order, reflecting lipid remodeling of the parental cell plasma membrane. Our data suggest that lipid emulsions differentially alter cell viability, monocyte composition and thereby microparticle release. While MCT have deleterious effects, we have shown that parenteral nutrition emulsion containing LCT or LCT and MCT associated to n‐3 and n‐9 fatty acids have no effect on endotoxin‐induced cell death and inflammation.